Open and Distance Learning: Engaging Learners through Innovation and Creativity - Wardah Mohamad; Rosmah Mohamed (2009)
Open learning has increased in importance over the years as seen in the increasing number of universities offering open and distance learning programmes. Research in the area has also increased over the years, covering a multitude of topics and concentrating on areas such as e-learning, interactive learning and collaborative learning. The authors of this research suggested that academics and practitioners should explore how teachers or tutors can influence learning designs and strategies with the aim of engaging learners through innovation and creativity. This paper explores the avenues that can be pursued by Open University Malaysia to incorporate innovation and creativity into its blended learning mode. Data were gathered from a literature review on open and distance learning, print module, online learning, and face-to-face tutorial. The research thus provides information on the current practices of open and distance learning programmes in Open University Malaysia; and the basic principles of implementing these open and distance learning programmes. In particular, the findings provide the characteristics of an effective print module, online learning, and face-to-face tutorial. At the end of the paper, some innovative and creative ideas that can be implemented in Open University Malaysia were suggested and discussed. (Authors' abstract)